A note on 4-dimensional locally conformally flat Walker manifolds - S. Azimpour; M. Chaichi; M. Toomanian (Հայաստանի ԳԱԱ)
A 4-dimensional Walker metric on a semi Riemanian manifold M, for the canonical metric with с = 0, have been investigated by M. Chaichi, E. Garcia- Rio and Y. Matsushita. The paper generalizes these notions to the case of constant с = 0. Specially the form of defining functions of this metric in locally conformally flat 4-dimensional Walker manifolds is found. 4-мерная метрика Уолкера на полу-римановом многообразии М, для канонической метрики с с = 0, было исследовано М. Чаичи, Э. Гарсия-Рио и И. Мацушита. В настоящей статье эти понятия обобщаются на случай постоянного с = 0. В частности, найден вид определяющих функций этой метрики в локально- конформно плоских 4-мерных многообразиях Уолкера.
Keywords: Mathematics; Science